The transcription factor EMB1444-like affects tomato fruit ripening by regulating YELLOW-FRUITED TOMATO 1, a core component of ethylene signaling transduction - Zhao, Weihua (Journal of experimental botany, 2023)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.